Analysis of Entrepreneurial Skills among Education Students: The Role of Family Background and Entrepreneurship Education across Five Skill Dimensions - Nadia Fika Hana; Leny Noviani (Journal of Educational Sciences, 2026)
Statistics Indonesia (BPS) data from 2022–2025 show an increase in educated unemployment among university graduates, highlighting a potential mismatch between higher education outcomes and labor market absorption. This study identifies entrepreneurial skills among university students and examines differences based on family background and entrepreneurial education across five dimensions: leadership, reflective communication, risk-taking, creativity and innovation, and future orientation. Using a quantitative approach, data were collected from 369 FKIP UNS students through an online questionnaire and analyzed using independent-samples t-tests and Mann–Whitney U tests. The results show that students' entrepreneurial skills are at a moderate level, indicating that efforts to strengthen entrepreneurial skills at FKIP UNS have not optimally promoted entrepreneurial career orientation. Family background and entrepreneurship education showed significant differences in entrepreneurial skills levels across all five dimensions: leadership, reflective communication, risk-taking, creativity and innovation, and future orientation. This indicates that students with an entrepreneurial family background tend to demonstrate higher entrepreneurial skills through experience, support, and direct interaction in business management activities. Meanwhile, students who had received entrepreneurship education demonstrated higher levels of entrepreneurial skills through structured learning processes within formal college education curricula.